Testing the accuracy of Coimbra Astronomical Observatory Solar Filament Historical Series (1929–1941) - Lourenço, Ana (2022)
The present work aims to validate the positions of solar filaments published in the Annals of Coimbra University Astronomical Observatory, currently the Geophysical and Astronomical Observatory of the University of Coimbra, corresponding to years 1929 to 1941. The published Stonyhurst positions were obtained by an original method devised in the early 20th century that used a spherical calculator instrument, a wood-made model of the Sun. We used the digital images of the original spectroheliograms to measure the positions of the filaments, and heliographic coordinates were determined with the routines implemented in the Python package Sunpy. The correlation coefficients between both sets of coordinates are positive and highly significant. The results validate the method used at the Coimbra observatory and the published data. We conclude that the Coimbra solar filament catalogues are reliable and can therefore be considered for future solar activity studies.